Magill's survey of world literature - Kellman, Steven G. 1947-; Magill, Frank N. (Frank Northen) 1907-1997 (Gale virtual reference library, 2009)
Offers profiles of major writers outside the United States from all time periods, accompanied by analysis of their significant titles of fiction, drama, poetry, and nonfiction.